Transfer of a single embryo versus drainage of subordinate follicles to prevent twin pregnancies in dairy cows. Why not both? - Fernando LÓPEZ-GATIUS; Irina GARCIA-ISPIERTO (The Society for Reproduction and Development, 2020)
In this study, we present two proposed approaches to prevent twin pregnancies in dairy cattle: 1) single, in vitro-produced embryonic transfer into a recipient cow or 2) subordinate follicle drainage at the time of insemination. Both procedures lead to improved embryonic survival. As the use of sexed semen generates herd replacements and additional heifers, we propose the transfer of a single female cattle embryo into cows that are not suitable for producing replacements, and follicular drainage in lactating cows with genetic merit. This should eliminate economic losses associated with twin pregnancies and increase cattle output of the herd.